2016
DOI: 10.17718/tojde.09231
|View full text |Cite
|
Sign up to set email alerts
|

COMMUNITY TRACKING IN A cMOOC AND NOMADIC LEARNER BEHAVIOR IDENTIFICATION ON A CONNECTIVIST RHIZOMATIC LEARNING NETWORK

Abstract: This article contributes to the literature on connectivism, connectivist MOOCs (cMOOCs) and rhizomatic learning by examining participant interactions, community formation and nomadic learner behavior in a particular cMOOC, #rhizo15, facilitated for 6 weeks by Dave Cormier. It further focuses on what we can learn by observing Twitter interactions particularly. As an explanatory mixed research design, Social Network Analysis and content analysis were employed for the purposes of the research. SNA is used at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 4 publications
1
29
0
3
Order By: Relevance
“…We also examined learners' participation by various technologies (technology network) by the social network of a space and around topic and topic generation process. Each of these approaches can be analysed and compared from both quantitative and qualitative perspectives (Skrypnyk et al, 2015;Bozkurt et al, 2016). This will be a future focus of our study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also examined learners' participation by various technologies (technology network) by the social network of a space and around topic and topic generation process. Each of these approaches can be analysed and compared from both quantitative and qualitative perspectives (Skrypnyk et al, 2015;Bozkurt et al, 2016). This will be a future focus of our study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Bozkurt and colleagues (2016) analysed interactions, community formation, and nomadic learner behavior in Twitter for a six-week long MOOC within a social network and Community of Inquiry framework. These studies have shown us how learners participate in cMOOCs from the information flow and community formulation perspectives; however, just as the author reported in their study, their limitation was that they only focused on the interaction in Twitter (Skrypnyk et al, 2015;Bozkurt et al, 2016). Though Twitter is one of the main media adopted by most participants, the cMOOC was also supported by the course website, blog, Facebook, and many other technologies.…”
Section: Cmoocs Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a variety of approaches was used to diagnose learning behavior in cMOOCs contexts, for instance, deductive analysis of qualitative data (Wang et al, ), content analytics (Wang et al, ) as well as social media analytics (Bozkurt et al, ), etc. Specifically, deductive qualitative analysis is often used to establish the framework of connection interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches that support discussion are to highlight content that contributes to learning by commenting on it, or asking learners to link to videos and photographs and then comment on these to initiate interactions. MOOC learners are often nomadic and will move between communities, forming sub-communities within those platforms, and hashtags can be used to bring those groups together (Bozkurt et al, 2016).…”
Section: Develop and Make Effective Use Of Appropriate Pedagogiesmentioning
confidence: 99%